Toughening of graphene oxide-epoxy nanocomposites by means of very high pressures and shear rates. (20th October 2020) - Munoz-Guijosa, J.M.; Fernández Zapico, G.; Peña-Rodríguez, O.; Akasaka, H.
Abstract: We have successfully conceived and demonstrated a simple, scalable procedure for toughening graphene oxide-epoxy nanocomposites without any reduction in other important mechanical parameters as stiffness or strength. The procedure takes advantage of the very high pressures and shear rates occurring in superior kinematic couples, in the order of GPa and 10 6 s −1, respectively. Fracture toughness and strength improvements of up to 220% and stiffness increases of up to 130% have been obtained with adequate process parameters. While the high shear rate contributes to a better nanofiller dispersion, the scissions produced by the applied energy promote the creation of longer precured polymer chains, and consequently to a reduced chemical crosslinking after curing, as well as an improved nanofiller – matrix interfacial adhesion. These hypotheses are corroborated by GPC measurements performed in the processed cured polymer, which reveal a substantial chain length, and creep compliance increases in the specimens processed with optimum parameters. Furthermore, Raman measurements in strained and not strained specimens show an improved nanofiller-matrix adhesion and a modification of the Csp 2 content in the graphene oxide, and SEM images show a substantially rougher fracture surface. NMR observations show no changes in the polymeric structure, suggesting the conservation of other non-mechanical properties. Graphical abstract: Image 1